Kompetensi Wanita Tani dalam Usahatani Rumput Laut di Desa Wasalabose Kecamatan Kulisusu Kabupaten Buton Utara - Rifal Rifal; Hartina Batoa; Putu Arimbawa (Fakultas Pertanian Universitas Halu Oleo, 2022)
The purpose of this research is to ascertain the technical proficiency of female farmers engaged in seaweed production as well as the link between these two factors. choosing a purposeful site for the study. The study was done throughout the month of November 2021. The participants in this research were female farmers who were engaged in seaweed farming in Wasalabose Village. Up to 23 persons were used in the sample selection during the census. Descriptive (interval with percentage) and Spearman Rank analyses were utilized in the data analysis. The findings demonstrated that Wasalabose Village, Kulisusu District, North Buton Regency women farmers had a high level of technical proficiency in seaweed cultivation. The factors of seed purchasing, seed selection, seed binding, site selection, and harvesting show the excellent technical proficiency of women farmers. Age, the number of dependents, and prior farming experience are characteristics of women farmers that have a significant association with their technical competence, however education level has no significant relationship with their technical skill whatsoever.